Jesus' mission and messianism through the prism of Islam and Christianity: Analysis of the Book of prophet Zechariah - Gološ Dževad (Kom: Časopis za Religijske Nauke)
The proof of Isa's (Jesus) prophethood and messiahship in Christianity is reflected in the fulfillment of the Old Testament prophecies that speak of the appearance and arrival of the Messiah. The Quranic principle of proving the truth of its text and content is not tied to any other book. The Quran proves its truthfulness, the fact that it is the last Revelation to Prophet Muhammed who was the last in a series of prophets, and its supernaturalism in a number of ways - through its language, style, stories about the past and the future, ethical and legal code, and other examples of the supernatural. In the scope of proving these truths in the same way, the Quran also proves Jesus' prophethood and messiahship. These are the two main differences in proving the truth in Islamic and Christian theology as regards prophethood and messiahship. As a critical review of Christian argumentation, we analysed the Old Testament book of prophet Zechariah, which contains three prophecies that Christian exegetes say refer to Jesus. From the point of view of Islam, the only way to prove Jesus' prophethood and messiahship is the Quran.